(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Twenty (20) apparently healthy growing Yankasa rams with a mean initial live weight of 20-21kg±0.5kg were used for 120 days feeding and 21 days digestibility trials to was carried out to determine nutrient digestibility and rumen metabolites profile of growing Yankasa rams. The animals were grouped into four with five animals each in a Completely Randomized Design (CRD) and randomly allocated to four treatments. The treatments were 2.5, 3.0, 3.5 and 4.0% body weight. The DM (88.38%), CP (89.70%), NDF (74.54%) and ADF (77.63%) were significantly (P<0.05) higher in animals fed 4% body weight. OM (87.27%) was significantly (P<0.05) higher at 3.0% body weight, but EE (90.14%) was significantly (P<0.05) higher in animals fed 3.5% body weight. Nutrient digestibility showed significant variation (P<0.05) across the treatments. Rumen pH was within the normal range (6.77-6.87). TVFA (Total volatile fatty acid) (24.67 Mmol/100ml) at 0hours was significantly (P<0.05) higher in animals fed 3.5% body weight while Rumen Ammonia nitrogen (NH4-N) (63mg/lt) at 4 hours of sampling was significantly (P<0.05) higher with animals fed 4% body weight. Therefore, it was concluded that feeding Brachiaria Mulato II based total mixed ration at 4% body weight increased Dry matter digestibility by 88.38% and Crude protein digestibility by 89.70% respectively. Livestock farmers are encouraged to feed Brachiaria Mulato II based total mixed ration at 60:40 ratio for improved utilization and normal rumen function.